Wednesday

April 16, 2014

April 16, 2014

Posted by **Arielle** on Tuesday, November 8, 2011 at 8:51am.

9^(2x)=11^(3x-2)

- Algebra II -
**Steve**, Tuesday, November 8, 2011 at 3:06pmtake logs to get rid of the exponents

2x ln9 = (3x-2)ln11

x(2 ln9 - 3 ln11) = -2 ln11

x = -2 ln11/(2 ln9 - 3 ln11)

x = -4.79/-2.8

x = 1.71

**Related Questions**

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

Chemistry - please check my answers for the following questions. 1) when a ...

Physics - Talking about significant figures, my Physics textbook lists 5 rules ...

Intermediate Algebra - Solve using the substitution method. Show your work. If ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

algebra - I am totally lost on how to solve g(x)=2x^2+3x-1 to find the y and x-...

Intermediate Algebra - Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x...

Algebra II - Solve: (2x – 3)(3x – 5) = 0 Solve by the quadratic formula. Leave ...

Math Systems - I cannot solve these last three systems. Could you show me the ...

algebra - solve the system 2x-y+z=3 x+3y-2x=11 3x-2y+4z=1